Education And Economic Development: A Historical Literature On Relations Between Human Capital And National Strategies - M. R., Abdul Hamid; Abdullah, Ibrahim (Centre for Promoting Ideas, USA, 2011)
The relation of human capital development towards generating robust economic development is closelylinked in ensuring our country’s progress are moving on the right track and to begin with, education aspect must be looked into. This could be seen as in the ninth Malaysia Plan that stresses on investment in human capital development. Therefore, this paper focuses on the meaning of human capital and its impact on the economic development, education and the national strategies. It is found that developing human capital is very much important indeed that prompted the government to give a due consideration towards this matter as the need to balance human capital development and the inner or spiritual strength of each and every Malaysian citizen is utmost vital. As outlined by the Prime Minister the balance was necessary especially from the aspects of adopting and maintaining high ethical values, which were important in Malaysia’s bid to compete with both developed and developing nations.